2005
DOI: 10.1525/mp.2005.23.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Cues for Key Perception of a Melody

Abstract: STUDIES HAVE SHOWN THAT PITCH SET, which refers to a set of pitches of constituent tones of a melody, is a primary cue for perceiving the key of a melody. The present study investigates whether characteristics other than pitch set function as additional cues for key perception. In Experiment 1, we asked 13 musicians with absolute p itch t o select k eys for 60 stim ulus t one sequences consisting of the same pitch set differing in pitch sequence. In Experiment 2, we asked 31 nonmusicians to select tonal center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
2
19
0
1
Order By: Relevance
“…However, the original idea of the pitch full-set does not entirely account for the finding that different key perceptions emerge for melodies that consist of the same six-pitch full-set but differ in the temporal arrangements of these pitches (e.g., Matsunaga & Abe, 2005). The present study addressed the temporal order issue by introducing the concept of changing pitch subsets (i.e., changing pitch set at each point) as an important property of melodic structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the original idea of the pitch full-set does not entirely account for the finding that different key perceptions emerge for melodies that consist of the same six-pitch full-set but differ in the temporal arrangements of these pitches (e.g., Matsunaga & Abe, 2005). The present study addressed the temporal order issue by introducing the concept of changing pitch subsets (i.e., changing pitch set at each point) as an important property of melodic structure.…”
Section: Discussionmentioning
confidence: 99%
“…Although AP musicians are often thought to be the special selected group, empirical studies have shown that tonal organization of AP musicians essentially shares the same characteristics with that of nonmusicians (e.g., Matsunaga & Abe, 2005;Temperly & Marvin, 2008). It is general that compared to responses of the nonmusician group, responses of the musician group can be less contaminated by extraneous factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on human subjects have been much more attentive to the influence of temporal ordering on perceptions of key than the key-finding literature. Since distributions collapse the temporal dimension, they implicitly assume that the temporal order of pitch-classes does not influence the sense of key, even though experimental studies such as [5], [6], and [17] have amply demonstrated the importance of temporal order to key inferences. Approaches to key finding that deal with modulation by using windowed analysis, such as Temperley's ( [23], [24]) and Sapp's ( [21]), may partially address this concern.…”
Section: Key Findingmentioning
confidence: 99%
“…Incluso más, observaron también que secuencias de eventos con la misma duración y frecuencia acumulada pueden o no promover un claro sentido tonal según cómo dichos eventos se ordenen en el tiempo. Y este mismo resultado fue reportado más recientemente por Matsunaga y Abe (2005), quienes examinaron un número más variado de secuencias y órdenes temporales. Estas evidencias sugieren, entonces, que el sentido de tonalidad surge de la información interválica provista por un pasaje u obra musical y, consecuentemente, que el contenido de la representación tonal es de naturaleza secuencial, y no acumulativa.…”
Section: La Tonalidad Según El Modelo De 'Acumulación De Clase De Eveunclassified